Qualitative assessment of ballet kinematics algorithm: case study in the glissade saut de chat - Benchetrit, A. (Journal of Dance Medicine & Science, 2025)
Background: Objective assessment of ballet execution remains limited by the subjective nature of expert evaluations, which often integrate stylistic interpretation and artistic expression.